PENGARUH LATIHAN UNDER THE BASKET SHOT SECARA BERANTING TERHADAP KEMAMPUAN SHOOTING PERMAINAN BOLA BASKET SMP NEGERI 8 PEKANBARU - Rifaldi, Ridho; Slamet, Slamet; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : This research was conducted to determine the effect of the Under The Basketball Shot training on the shooting ability of the men's basketball team in Pekanbaru 8 Middle School. At the time of the match many shots into the basketball hoop were missed and failed to score points. Basketball player shots are still not good because there are many opportunities to shoot but not many have made it into the ring. This is because the ability to shoot players still needs to be trained. The form of this research is experimental treatment, with the population of the men's basketball team in the State Junior High School 8 Pekanbaru, the data in this study are active male team players at Pekanbaru 8 Middle School, totaling 10 people. The instrument carried out in this study is to use a 30-second shooting test that aims to measure shooting ability. After that, the data was processed with statistics, to test the normality with the lilliefors test at a significant level of ∝ 0.05. The hypothesis proposed is the influence of the under the basketball training on the shooting ability of the men's basketball team at Pekanbaru State Middle 8. Based on the analysis of the t test it produces a T count of 3.62 and T table 1,833 which means T count> T table. Based on statistical data analysis, there is an average Pre-Test of 8.70 and the post-test average is 11.20 and the data is normal. Thus, it can be concluded that there is an influence of the under the basketball shot on the shooting ability of the men's basketball team at Pekanbaru 8 Middle School.Key Words :Under The Basketball Shot, Shooting Ability